The role of Islamic financial institutions in facing socio-economic problems during the covid-19 pandemic - Yetti Afrida Indra; Herlina Yustati (NUsantara Islamic Economic Journal, 2022)
This research was established of knowing the action in which the Sharia Financial Organizations could take facing economic social problems in the Covid-19 era in Indonesia. This research used qualitative-descriptive approach method with the technique of data collections. The data collections which was analyzing written sources such as scientiﬁc journal, literature review, books, mass media articles which talked about this issue and the documents which were related to the object of this research. The data were analyzed with data reduction technique by collecting the data based on the regulation, displaying the data by analyzing them based on research methods and then concluding the data to simplify the discussion. The result of this research is explaining the responsibility of Sharia ﬁnances institute facing economic social problems in the Covid-19 era. Which is as the action of the role of sharia banking which is as the distributor of government social activity, facilitating the distribution of ﬁnancing such as KUR and providing installment relief, serving customers through digital bank services, the role of Islamic pawnshops with restructuring and relaxation of credit, pawn care with 0% interest and distribution of interest subsidies to MSMEs. Provide funds with a special system in accordance with the conditions of the community, especially in small towns and villages. and the role of BMT as a social intermediary institution by collecting ZISWAF and conducting ﬁnancial stimulation such as distributing qardhul Hasan ﬁnancing, facilitating the cooperation agreement (Mudharabah) they can help the MSMEs to continue our business in the condition in Covid-19.